Large-mode-area multicore Yb-doped fiber for an efficient high power 976 nm laser - Li, Huizi (2022)
We present an efficient 976 nm laser generation from an ytterbium (Yb)-doped step-index multicore fiber (MCF) with six cores placed in a ring shape. Each of the six cores has a large-mode-area (LMA) and a low numerical aperture (NA), which makes the MCF equipped with the features of a large core-to-cladding area ratio and differential bending loss for wavelength and mode selection. Hence, the Yb-doped MCF benefits 976 nm laser generation by simultaneously suppressing unwanted 1030 nm emission and higher-order modes (HOMs). A 976 nm laser is obtained in a short piece (88 cm) of the Yb MCF, with a good slope efficiency of 46% with respect to launched pump power and the maximum output power of 25 W (pump power limited). A mode area of 1432 µm2 at the 976 nm is expected for the fundamental in-phase mode.